Automatic detection of defective rail anchors - Khan, Rubayat Ahmed; Islam, Samiul; Biswas, Rubel (2017)
This conference paper was presented in 17th IEEE International Conference on Intelligent Transportation Systems, ITSC 2014; Qingdao; China; 8 October 2014 through 11 October 2014 [© 2014 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ITSC.2014.6957919